Activity of Local Countryside and Collectors in Turkestan - Rakhmatullaev Akhadulla (Zien Journals, 2022)
In this article, research was conducted on the activities of local historians and collectors in the territory of Turkestan. Until the 20s of the 20th century, a lot of materials related to the study of Turkestan were collected by the efforts of scientists and Turkic amateurs. The scientific study of the history of Central Asia, including Turkestan, was created and deepened only as a result of effective and selfless work at the beginning of our century and in subsequent years
Keywords: Local historians; scientists; ancient places; holy places